INFORMATION TECHNOLOGY CAPABILITY AND CORPORATE COMMUNICATION IN SME FOOD INDUSTRIES (Journal of Technology and Operations Management, 2019)
During this decade, technology has been recognized as one of the important factors for maintaining competitiveness in a global business environment. Malaysia, as a developing country, is moving towards to become internationally technological based manufacturing sectors using technological capabilities. Since the productivity of the organization is highly dependent on the technology capability, managers need to do their best to communicate effectively with their employees in order to facilitate the sharing information that substantially for contribute to the commercial success. Communication is important in connecting employees and employers, or employees and customers in the process of services in manufacturing. Due to an increase in global competition, rapid technological development and changes in customer demand, this makes the performance of food and beverage firms (F&B) has become increasingly dependent on continuous improvements to introduce new products and processes. Therefore, this study interested to focus on the information technology and corporate communication that has been considered as a pre-quisite to improve productivity in food industries. Even though technology is widely implemented and studied in many industries by researchers, IT capability in manufacturing industry is limited and indicated a major gap in SME’s. Furthermore, IT capability highlights the importance in SME’s. This study is a survey research and quantitative research. There are two methods for collecting data that are through an online survey and the distribution of a questionnaire through several manufacturing firms. Due to the importance of the services in the manufacturing sector, this study to explore the contribution towards the business development in manufacturing industries. Hence, the study also discusses the role of IT capabilities in supporting manufacturing practices, especially in the context of food industries.